menu search
brightness_auto
Feel free to answer or ask any questions.
If you are new here please see how to use or FAQ.
more_vert

For the circuit given below, the Kirchoff's loop rule for the loop BCDEB is given by the equation

(1) –i2R2 + E2 + E3 + i3R1 = 0 

(2) –i2R2 + E2 – E3 + i3R1 = 0 

(3) i2R2 + E2 – E3 – i3R1 = 0 

(4) i2R2 + E2 + E3 + i3R1 = 0

thumb_up_off_alt 3 like thumb_down_off_alt 0 dislike

1 Answer

more_vert
 
done_all
Best answer

Ans: (3) i2R2 + E2 – E3 – i3R1 = 0

Sol. In a loop BCDEB by KVL 

VB – i2R2 – E2 + E3 + i3R1 = VB 

i2R2 + E2 – E3 – i3R1 = 0

thumb_up_off_alt 2 like thumb_down_off_alt 0 dislike
...